SERVICES OF THE SURABAYA CITY ENVIRONMENTAL SERVICE IN SUPPORTING SUSTAINABLE DEVELOPMENT THROUGH CONTROLLING WASTE INTO THE SEA - Paulus Kohar; Sri Roekminiati; Ika Devy Pramudiana (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the services of the Surabaya City Environmental Agency (DLH) in supporting sustainable development through controlling waste into the sea based on the principles of good governance. The background of this study is based on the urgency of the problem of coastal water pollution in Surabaya City due to the discharge of domestic and industrial waste that has not been fully controlled, resulting in a decline in the quality of the marine ecosystem and the welfare of coastal communities. This condition demands an in-depth evaluation of the quality of local government services in managing waste based on the principles of good governance. The study used a qualitative descriptive method with a case study approach. Data were obtained through in-depth interviews, field observations, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that the transparency of the Surabaya City DLH services has been running quite well through the provision of information on digital media and socialization activities, although access to real-time environmental data is still limited. Service responsiveness is quite good with the availability of various public complaint channels, but is still hampered by limited personnel and monitoring technology. The effectiveness and efficiency of services are demonstrated by an increase in the Water Quality Index (IKA) from 52 in 2022 to 61 in 2025, as well as an increase in the number of communal wastewater treatment plants (WWTPs) from 48 to 79. The novelty of this research lies in the integrated analysis of three dimensions of good governance in the context of urban coastal waste management services in Surabaya, a context that has not been widely studied specifically in Indonesia.